Exploring the diastereoselectivity for Fischer indolization of L-menthone under different conditions, spectral characterization, and biological activities of new (2R,4aS)-2,3,4,4a-tetrahydro-1H-carbazole analogs - Younus, Munisaa; Ahsan, Marium; Huda, Noor-ul; Khan, Maria Aqeel; Rasheed, Saima; Sadiq, Rabia; Basha, Fatima Zehra (European Journal of Chemistry, 2022)
Tetrahydrocarbazoles are important class of heterocycles that exhibit numerous biological properties. They are also found in several natural products. In the present study, Fischer indolization of L-menthone was investigated for diastereoselectivity using different reaction conditions. No appreciable diastereoselectivity was observed for the acids used except CuBr and boric acid at varying temperatures, where satisfactory results were obtained. In addition, a small library of new (2R,4aS)-2,3,4,4a-tetrahydro-1H-carbazole analogs was reported and structurally characterized using spectroscopic techniques herein. Additionally, the compounds were evaluated against different biological activities, such as carbonic anhydrase inhibitory, immunomodulatory, and anticancer activities and did not show any activity. As the synthesized library was found safe when tested against cytotoxicity in normal cell line, it will be explored for other biological activities in near future to identify its biological outcome.